Improvement of fertility and hatchability of artificially incubated ostrich eggs in the little Karoo - Van Schalkwyk, Salmon Jacobus (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1998)
Ostriches are an important commercial species in South Africa and are becoming increasingly so in other parts of the world. Fertility and hatchability of artificially incubated ostrich eggs, however, is generally regarded as low compared to other poultry species and to ostriches in the wild. Investigation into specific farming practices at present indicated scope for an overall improvement in productivity through a sound breeding strategy. This thesis investigated factors that affect egg production, fertility, and hatchability of artificially incubated eggs in the Little Karoo region of South Africa. Specific breeding pair combinations accounted for the major variations in egg weight, hatchability, chick production and offspring weight at slaughter age. An appreciable proportion of variation in reproductive traits was attributable to the repeatable nature of breeding pair performance from year to year, even from first breeding attempts, suggesting that selection of good breeding stock can be made from an early age. Artificially incubated eggs showed improved hatchability when eggs were collected two to three hours after lay rather than the following morning. Storing position of eggs did not significantly effect hatchability when eggs were stored for a maximum of one week. The critical zero temperature for ostrich eggs, below which no embryonical development takes place, was found to be ± 25°C and cooling eggs to temperatures below 20°C for complete cessation of embryonic development during storage resulted in better hatchabilities compared to eggs stored at 25°C room temperature. Hatchability decreased when incubator temperatures were raised from 36 to 37.3°C. Large temperature fluctuations and gradients, which encompass detrimental temperatures, persist within forced draught wooden incubators of the type most commonly in use in the Little Karoo region. The highest temperatures occurred at the top of these incubators and will consequently have a negative impact on hatchability. The ontogeny of ostrich egg metabolism showed an exponential increase during the first 70% of incubation followed by a decline to 75% of the peak value between days 31 and 38 of incubation. From peak levels of embryonic development it was calculated that single stage incubators needs an airflow of 54.4 1/egg.hour to maintain oxygen levels just below 21% and carbon dioxide levels below 0.5%. Lower embryonic mortalities were observed when eggs were turned twenty-four times/day in an electronic incubator compared to hand turning twice a day. Eggs rotated through increasing angles between 60 and 90° resulted in a linear improvement in hatchability. In incubators where turning angles were fixed at 60°, lower hatchabilities were overcome by incubating eggs for 2 - 3 weeks in a horizontal position before placing them vertically. No specific farming practice could be singled out as the main cause of low fertility or hatchability but rather a combination of certain practices applied wrongly.
Keywords: Ostrich farming -- South Africa; Eggs -- Hatchability; Eggs -- Incubation